Nilai- Nilai Edukatif Upah-Upah Mandailing Dalam Perspektif Pendidikan Karakter - Ahmad Husein,; Salsabila Nasution ,; Anggun Paraditha,; Riski Saskia Ray ,; Nur Mawaddah, (Jejak digital: Jurnal Ilmiah Multidisiplin, 2025)
This study explores the educational values embedded in the Upah-Upah or Mangupa tradition of the Mandailing community from the perspective of character education. This cultural practice, often marginalized by modernization, contains profound moral, spiritual, and social values that are essential for nation-building. The purpose of this study is to identify the philosophical meanings and educational values within the Upah-Upah ceremony and to analyze their relationship with Thomas Lickona’s character education theory. The research employs a qualitative descriptive approach using library research methods, analyzing books, articles, and journals on Mandailing culture and character education. The findings indicate that Upah-Upah functions as a symbolic, spiritual, and social medium that embodies values of religiosity, responsibility, cooperation, respect, and cultural pride. These values align with Lickona’s three dimensions of character moral knowing, moral feeling, and moral action. Thus, the Upah-Upah tradition can serve as a model for locally based character education that strengthens national identity and moral values in the face of modern challenges..